Autocrine VEGF Isoforms Differentially Regulate Endothelial Cell Behavior - Yamamoto, Hideki; Rundqvist, Helene; Branco, Cristina; Johnson, Randall S. (Frontiers in Cell and Developmental Biology, 2016)
Vascular endothelial growth factor A (VEGF) is involved in all the essential biology of endothelial cells, from proliferation to vessel function, by mediating intercellular interactions and monolayer integrity. It is expressed as three major alternative spliced variants. In mice, these are VEGF120, VEGF164, and VEGF188, each with different affinities for extracellular matrices and cell surfaces, depending on the inclusion of heparin-binding sites, encoded by exons 6 and 7. To determine the role of each VEGF isoform in endothelial homeostasis, we compared phenotypes of primary endothelial cells isolated from lungs of mice expressing single VEGF isoforms in normoxic and hypoxic conditions. The differential expression and distribution of VEGF isoforms affect endothelial cell functions, such as proliferation, adhesion, migration and integrity, which are dependent on the stability of and affinity to VEGF receptor 2 (VEGFR2). We found a correlation between autocrine VEGF164 and VEGFR2 stability, which is also associated with increased expression of proteins involved in cell adhesion. Endothelial cells expressing only VEGF188, which localizes to extracellular matrices or cell surfaces, presented a mesenchymal morphology and weakened monolayer integrity. Cells expressing only VEGF120 lacked stable VEGFR2 and dysfunctional downstream processes, rendering the cells unviable. Endothelial cells expressing these different isoforms in isolation also had differing rates of apoptosis, proliferation, and signaling via nitric oxide (NO) synthesis. These data indicate that autocrine signaling of each VEGF isoform has unique functions on endothelial homeostasis and response to hypoxia, due to both distinct VEGF distribution and VEGFR2 stability, which appears to be, at least partly, affected by differential NO production. This study demonstrates that each autocrine VEGF isoform has a distinct effect on downstream functions, namely VEGFR2-regulated endothelial cell homeostasis in normoxia and hypoxia.